Legal Protection for Individual Entrepreneurs Through Regulatory Reform in Uzbekistan - Aybek Bakhramovich Yakubov; Nargiza Doroyevna Raimova; Uktamjon Zarifjon ugli Tukhtaev; Mavludbek Mukimkon ugli Ismoilov; Shokhrukh Islomjon ugli Gulomov (Journal of Human Rights, Culture and Legal System, 2026)
The individual entrepreneurship sector in Uzbekistan has experienced rapid growth and has become one of the key pillars of national economic development. However, in practice, individual entrepreneurs continue to face various legal and administrative obstacles that may hinder business growth and sustainability. This situation raises questions regarding the effectiveness of existing policies and regulations in protecting the rights of individual entrepreneurs. This study aims to first, analyze the existing legal framework for the protection of individual entrepreneurship rights in Uzbekistan; second, identify the ideal regulatory model for protecting the rights of individual entrepreneurs in the United Kingdom, a country that has successfully implemented progressive entrepreneurial regulatory reforms; and third, formulate recommendations for regulatory reform concerning individual entrepreneurship in Uzbekistan. This research employs a normative legal research method using statutory, conceptual, and comparative approaches. The findings indicate that first, the protection of individual entrepreneurs’ rights in Uzbekistan remains constrained by several factors, including regulatory inconsistencies, weak law enforcement, complex bureaucratic procedures, corruption practices, and limited legal awareness among business actors. Second, the United Kingdom has developed a comprehensive protection model that combines regulatory certainty, social protection, and effective business risk management through transparent regulations, accessible dispute resolution mechanisms, and business support services. Third, this study argues that comprehensive regulatory reform is necessary through regulatory harmonization, strengthening law enforcement institutions, enhancing bureaucratic transparency, and promoting a stronger legal culture. Such reforms are expected to improve legal certainty and provide more effective protection for individual entrepreneurs in Uzbekistan